U.S. Telco Industry History as a Prologue to its Future - McDonough, Carol C (Journal of Telecommunications and the Digital Economy, 2017)
The United States telco industry has been shaped by the interplay of technological advance, free enterprise, politics, public pressure, and government regulation. The history of the industry reveals a continuing tension between the forces of competition and concentration. Having coursed through eras of monopoly, competition, and regulated monopoly, the telcos are now in a more competitive arena. There is regulatory uncertainty on the issue of net neutrality.